Therapeutic Potential of Autophagy in Glioblastoma Treatment With Phosphoinositide 3-Kinase/Protein Kinase B/Mammalian Target of Rapamycin Signaling Pathway Inhibitors - Xia, Qin; Xu, Mengchuan; Zhang, Pei; Liu, Liqun; Meng, Xinyi; Dong, Lei (Frontiers in Oncology, 2020)
Glioblastoma (GB) is the most malignant and aggressive brain tumor, characterized by frequent hyperactivation of the PI3K/AKT/mTOR signaling pathway. PI3K/AKT/mTOR inhibitors is a promising clinical efficacy theoretically. However, strong drug resistance is developed in GB against PI3K/AKT/mTOR inhibitors due to cytoprotective effect and adaptive response of autophagy during the treatment of GB. Activation of autophagy by PI3K/AKT/mTOR inhibitors not only enhance treatment sensitivity, but also leads to cell survival when drug resistance develops in cancer cells. In this review, we analyze how to increase the anti-tumor effect of PI3K/AKT/mTOR inhibitors in GB treatment, which is achieved by various mechanisms, among which targeting autophagy is an important mechanism. We review the dual role of autophagy both in GB therapy and resistance against inhibitors of the PI3K/AKT/mTOR signaling pathway, and further discuss the possibility of using combinations of autophagy and PI3K/AKT/mTOR inhibitors to improve the treatment efficacy for GB. Finally, we provide new perspectives for targeting autophagy in GB therapy.